'In and Against the State'? Venezuela's Education Missions and the Struggle for a Democratic Alternative. Issue 8 (3rd August 2017) - Duffy, Maura
ABSTRACT: In Latin America, dissatisfaction with neoliberal democracy has led to a search for alternatives based on more participatory forms of citizen engagement that have overtly pedagogical dimensions. This paper focuses on Venezuela's Adult Education Missions to illustrate the possibility but also the inherent contradictions of education 'in and against the state' to enhance grassroots critical consciousness and mobilisation. It argues that while considerable progress has been made at the micro level, structural change from above to redistribute power and transform capitalist relations of production has been insufficient and that this threatens the future of the project for radical social change.